Footprint of Covid-19 Pandemic and the Managerial Approach to Enhancing Nigerian Workers’ Productivity - Opaleke , Jeremiah Babajide (Interdisciplinary Journal Of Lifelong Learning, 2025)
One of the remarkable events of recent past is outbreak of coronal virus pandemic (COVID-19) that shook the global economy. Multiplier effect of the pandemic spurs this study to investigate footprint of COVID-19 pandemic and the managerial approach to enhancing Nigerian workers’ productivity. This study is a quantitative research design that x-rays role of labour motivation through compensatory approach on Nigerian workers’ productive contributions. It is a study built on three (3) management theories: Pandemic Management Theory; Event System Theory; and Scientific Management Theory, which were tested to assist ascertain their propositions. Population examined in this study is a mixture of management and staff of public and private Nigerian manufacturing and service providing corporate institutions. The population size is of Two thousand, one hundred and forty-five (2,145) respondents, while adopted sample size, to avoid spurious results, is of a total of Three hundred and thirty-seven (337) purposively and randomly collected samples. Data used in this study were mixture of primary and secondary data, which was collected through well-structured questionnaire and corporate information of the sampled Institutions. Data were analysed, using inferential statistics, Granger’s causality and relationship mechanism, panel data regression approach, and the t-test results’ reliability tools, so as to ascertain the validity and the reliability of the study’ outcomes. And in all of it, the study therefore revealed that significant but negative uni-directional causal relationship exists between COVID-19 and Nigerian workers’ productivity. Also, the study revealed that strategic motivation through compensatory managerial means has positive and significant impact on Nigerian workers’ productivity; as evident in the β-coefficient value of 0.534. And it was therefore on this premise, that the study concluded so, and then recommended that the managers of human resource in all the sectors of the Nigerian economy, should always be guided in their institutional planning and labour policy management, going by the revelations of this study, by setting out risk management mechanisms that will protect their work-forces from geographical unforeseen and health uncertainties (pandemic). Also, corporate managers should adopt motivation techniques through compensatory means as a clue and mechanism to job performance enhancement. This approach will gravely assist the nation in building quality productive and sustainable output system.